RANCANGAN SISTEM INFORMASI PT. DAYA MOTOR JAMBI MENGGUNAKAN APLIKASI BERBASIS WEB - Elzas - (JURNAL AKADEMIKA)
Information systems can assist in the work of requires handling routine and rapid site -based data. In place of this research is PT . Motor power Jambi , while the author has conducted research in the application of information system which is specialized in designing online promotion system at PT . Motor power Jambi using Macromedia Dreamweaver 8 , which they have done by distributing promotional brochures to every person they meet. And in data processing sales are still using Microsoft Excel and Word . By analyzing the current system there are some shortcomings that affect the smooth operation of information systems and slow data transmission. This system design using Macromedia Dreamweaver 8 program , the website designing is expected to assist in the promotion and sale of data processing and can reduce problems in the handling of sales data and information required faster